Value Chain Performance of Cocoa Beans in Banjaroya, Kulon Progo - Wildan Fajar Bachtiar; Galih Kusuma Aji; Diklusari Isnarosi Norsita (Gontor AGROTECH Science Journal, 2019)
Kulon Progo is the area with the largest cultivation area for cocoa commodity in Special Region of Yogyakarta, which is 3,522 Ha [Goverment Database Statistics, 2013]. This study was conducted to analyze the performance of the value chain of cocoa beans. The data used in this study was the primary data obtained depth interviews with respondents from; farmers, farmer groups, cooperatives, companies and consumers. The method used to analyze in this study was the economic value added method. From the result, the highest revenue was found in the sales of the fermented dry cocoa seeds which was about 15.47; this showed that it is necessary for the farmers to apply the fermentation process to their cocoa products in order to boost their value and get bigger revenue. But the problem was the farmers need more time for the fermentation process as well as spending more money in buying fermentation box which are needed for the fermentation process. The sales of wet or non-fermented dry cacao seeds actually have low R/C value but farmers just do not want to bother themselves with the fermentation process so they end up in selling their products in wet or non-fermented dry state. Meanwhile, the process of making chocolate bar product has not given much value yet; eventhough this process should be able to give more value, considering the price for every kg of chocolate bar is around 65,000 Rupiahs. In this case, the cost for the cacao processing machine became the depression burden which cannot be covered by the amount of the cacao products produced by farmers. The solution for this problem can be done by conducting a collective purchase through Koperasi level; by doing this the farmers can enlarge their production scale which will end up in increasing their products' R/C value